https://doi.org/10.46889/JRMBR.2025.6203 - Alison A Smith (Journal of Regenerative Medicine & Biology Research, 2025)
Objective: Stem cells play a pivotal role in wound healing. Understanding the interplay of chemical signals governing wound healing in different settings could inform on novel strategies to improve outcomes. Before examining wound responses to targeted supplementation of anti-inflammatory or pro-angiogenic treatments, components of the wound secretome should be analyzed at various phases of healing. This study aimed to evaluate the differences in the wound secretome produced by MSCs from severe knee Osteoarthritis (kOA) versus acutely inflamed patients (infections and trauma requiring amputations). We hypothesized that bone marrow-derived Mesenchymal Stem Cells (MSCs) from patients requiring amputation would secrete a higher level of pro-inflammatory cytokines compared to MSCs from patients with chronic diseases such as kOA. Methods: Bone marrow was processed with density-gradient centrifugation. MSCs phonetypes were confirmed by surface CD34, CD45, CD73, CD90 and CD105 expressions using flow cytometry. Supernatants were collected after 40 hours of cell culture. Milliplex Human Cytokine/Chemokine/Growth Factor Panel A kit was used to measure pro-inflammatory (IL1β, IL6, IL8, IL17A and MCP1); anti-inflammatory (IL4 and IL10); immunomodulatory (FGF-2) and pro-angiogenic (VEGF) factors. Data were analyzed with Bioplex200 Manager and Mann-Whitney U tests performed with α=0.05. Results: A total of 12 patients were enrolled in this IRB-approved study with 7 (58%) who had undergone Total Joint Replacement (TJR) for kOA and 5 (42%) who had non-limb salvageable injuries from acute traumatic or infectious etiologies requiring below or above-the-knee amputations. The mean age and BMI were 68.1 ± 7.6 years and 30.8 ± 2.9 kg/m2 for the kOA group and 56.2 ± 9.42 years and 32.8 ± 7.3kg/m2 for the acute group. 29% of patients in the kOA group were male compared to 80% of the trauma group. Similarly, 70% and 60% of patients in the kOA and trauma groups identified as White respectively. Compared to MSCs from kOA patients, significantly higher concentrations of the pro-inflammatory IL-6, IL-8, IL-17A and MCP-1 and anti-inflammatory IL-10 were secreted into the culture media by MSCs from the acutely ill patients. Conclusion: MSCs from acutely injured and infected patients produced significantly higher concentrations of four pro-inflammatory cytokines (IL-6, IL-8, IL-17A, MCP-1) and one potent anti-inflammatory cytokine, IL-10. These findings can provide insight into targeted regulation of acute inflammation and the healing response. Key Messages: Cytokines, chemokines and growth factors are drivers of inflammatory process guiding wound healing and tissue repair. The secretomes of Mesenchymal Stem Cells (MSCs) derived from tibial bone marrow of patients with acute injuries requiring amputation and patients with end-stage knee Osteoarthritis (kOA) undergoing Total Joint Replacement (TJR) were evaluated in this study to better understand the mechanisms influencing wound healing in acute versus chronic inflammatory settings.